2017
DOI: 10.18335/region.v4i3.167
|View full text |Cite
|
Sign up to set email alerts
|

Panel Data Models of New Firm Formation in New England

Abstract: Abstract. This study examines the impact of the determinants of new firm formation in New England at the county level from 1999 to 2009. Based on the Spatial Durbin panel model that accounts for spillover effects, it is found that population density and human capital positively affect single-unit firm births within a county and its neighbors. Population growth rate also exerts a significant positive impact on new firm formation, but most of the effect is from spatial spillovers. On the contrary, the ratio of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Rupasingha and Goetz (2011) found that self-employment rates are associated with poverty reduction in nonmetropolitan counties but not in metropolitan areas. Average establishment size is often found to be negatively associated with regional start-up activities in that clustering of smaller establishments may signify a friendly environment for business entry (Acs & Armington, 2006; Chinitz, 1961; Glaeser et al, 2010; Parajuli & Haynes, 2017; Qian, 2017a, 2017b). Moreover, the presence of industrial clusters represents competitive advantage for regions (Porter, 1998) and contributes to the success of entrepreneurs (Delgado et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rupasingha and Goetz (2011) found that self-employment rates are associated with poverty reduction in nonmetropolitan counties but not in metropolitan areas. Average establishment size is often found to be negatively associated with regional start-up activities in that clustering of smaller establishments may signify a friendly environment for business entry (Acs & Armington, 2006; Chinitz, 1961; Glaeser et al, 2010; Parajuli & Haynes, 2017; Qian, 2017a, 2017b). Moreover, the presence of industrial clusters represents competitive advantage for regions (Porter, 1998) and contributes to the success of entrepreneurs (Delgado et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the notation of Parajuli and Haynes (2017) and based on the values of ρ and λ different models can be specified:…”
Section: Modelmentioning
confidence: 99%
“…The range of variables included in recent logistics firm location models, such as gross domestic product (GDP) (Guerin et al 2021), population density and accessibility to residential population and manufacturing (Sakai et al 2020) and urban structure (Holl, Mariotti 2018), suggests that researchers are beginning to think beyond infrastructure density to broader factors that affect regional TW competitiveness. In the U.S. context, rural areas can be more attractive to certain types of firms because wages, property taxes, and land costs are all lower than in most metro areas (Parajuli, Haynes 2017, Wilkerson 2001.…”
Section: Literature Reviewmentioning
confidence: 99%